Deviant peers: Does friendship stability condition the peer-delinquency link? - Ouellet, Marie (European journal of criminology, 2023)
Prior research demonstrates a clear association between deviant peers and delinquent behavior, but it is unclear whether stable relationships provide stronger sources of influence than ephemeral ties. The current study addresses this gap by testing whether individuals are more likely to adjust their delinquent behaviors to be similar to their stable friends compared to their transient affiliations. Drawing from network data in the National Longitudinal Study of Adolescent to Adult Health, we use Stochastic Actor Oriented Models to estimate whether stable friendships condition the peer-delinquency link. Our results suggest the stability of friendships does not impact whether an individual will adopt the delinquency of their friends; adolescents were not more or less likely to conform to their stable and enduring friends compared to their transient and short-lived ties. We discuss the study's implications for understanding peer effects and status-seeking behaviors during adolescence.